Islamic Label and Stock Price Crash Risk - Bambang Sutrisno; Irwan Trinugroho; Taufiq Arifin; Tastaftiyan Risfandy (Journal of Islamic Monetary Economics and Finance, 2025)
This study explores how an Islamic label on firms influences stock price crash risk in Indonesia. We utilize a sample of 566 nonfinancial firms listed between 2016 and 2021, apply panel data method, and find that the Islamic label benefits the firms by lowering crash risk. Investors consider firms with the Islamic label as lower risk due to leverage constraints they must adhere to, which contributes to a decreased crash risk. Our primary results are robust to various sensitivity analyses. We also find that dividend policy and audit quality strengthen the Islamic label-crash risk nexus. The COVID-19 pandemic weakens the link between the Islamic label and crash risk. Furthermore, the Islamic label-crash risk nexus persists for up to two years.